Dıfferentıatıon of polıtıcal opınıons among the Alevı youth ın Istanbul - Mahir, Yunus Emre (My University, 2016)
İSTANBUL’DA YAŞAYAN ALEVİ GENÇLER ARASINDA SİYASAL KANAATLERİN FARKLILAŞMASI Bu çalışmada, kentli Alevi gençlerin siyasal eylemlilik çeşitleri ve seviyeleri ile siyasal kanaatlerinin kendi aralarında farklılaşmasının boyutları etnik, sınıfsal, demografik ve sosyo-ekonomik farklılıklar dikkate alınarak ortaya konulmuştur. Bu amaçla İstanbulda yaşayan Alevi olan veya Alevi ailelerden gelen 380 genç ile anket yapılmıştır. Araştırma sonuçları, ilgili farklılıklar dikkate alınacak şekilde tablolaştırılarak analiz edilmiştir. Buna ek olarak, Pierre Bourdieu’nun önerdiği toplumsal alan modeli dikkate alınarak, Alevi gençlerin Türkiye siyasal alanındaki konumları çoklu mütekabiliyet analizi yöntemi ile haritalandırılmıştır. Araştırmanın sonucunda Alevi gençler arasındaki etnik ve dinsel farklılıkların siyasi ideolojiler bağlamında ifade bulduğu, sınıfsal farklılıkların ise siyasal eylemlilik düzey ve çeşitleri üzerinde etkili olduğu ortaya konmuştur. Aleviler, Gençlik, Din ve Siyaset, Siyasal Alan

DIFFERENTIATION OF POLITICAL OPINIONS AMONG THE ALEVI YOUTH IN ISTANBUL This study explores the dimensions of differentiation in the forms and levels of political activism and in the political opinions of the urban Alevi youth by considering their ethnic, class, demographic and socio-economic differences. For this purpose, a survey conducted with 380 Alevi youth who live in Istanbul. The results of the survey were tabled and analyzed by taking the relevant differences into account. In addition, by taking into account the social field model proposed by Pierre Bourdieu, the positions of Alevi youth in the political field of Turkey have been mapped by using the method of multiple correspondence analysis. As a result of the research, it was found that the ethnic and religious differences among Alevi youth are expressed in the context of political ideologies, whereas the socio-economical differences are determinant on the intensity and forms of political activities. Alevis, Youth, Religion and Politics, Political Field
Keywords: Alevi gençler; Aleviler; Siyasi yönler; Türkiye